Atomic scale characterization of complex stacking faults and their configurations in cold deformed Fe42Mn38Co10Cr10 high-entropy alloy. (15th October 2020) - Qi, L.; Liu, C.Q.; Chen, H.W.; Nie, J.F.
Abstract: Atomic-resolution scanning transmission electron microscopy is used to study stacking faults and their configurations formed in cold deformed samples of a face-centered cubic (FCC) Fe42 Mn38 Co10 Cr10 (at.%) high-entropy alloy (HEA). It is found that the deformed microstructures contain at least four types of intrinsic stacking faults and two types of extrinsic stacking faults that are bounded by different partial dislocations, including Shockley, Frank and unusual 1/6<411> partials. Additionally, seventeen types of stacking fault configurations are also found, including the well-known Lomer-Cottrell lock, Hirth lock and faulted dipole, the rarely reported intrinsic-extrinsic fault bend, and thirteen hitherto unreported configurations containing different stacking faults and partial dislocations. Among these seventeen configurations, fifteen of them are constructed by conjugate stacking faults connecting at their edges, with a stair-rod partial belonging to 1/6<110>, 1/3<110> or 1/3<100> lying at every joint point of the stacking faults; and the rest two configurations have two intersecting stacking faults but contain different stair-rod dipoles at the intersection. Fourteen of these configurations are all comprised exclusively of intrinsic stacking faults, while three of them consist of a mixture of intrinsic and extrinsic stacking faults. Moreover, three out of the seventeen configurations contain surprisingly a Frank partial at one edge, in contrast to previously reported configurations that are all bounded exclusively by Shockley partials. Based on Burgers vector analysis, the formation mechanisms of the six types of stacking faults and the seventeen types of configurations are proposed and discussed. Graphical abstract: Image, graphical abstract